2018
DOI: 10.3389/fmars.2018.00439
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Commercial and Recreational Fishers on the Potential Ecological Impacts of the Block Island Wind Farm (US)

Abstract: Offshore wind is gaining momentum in the United States as a viable source for meeting domestic energy needs. Although offshore wind farms have been developed in Europe and Asia, the Block Island Wind Farm (BIWF) is the first offshore wind farm built in North America. To improve marine resource management, it is critical to understand the impacts of the wind farm on marine resource users in context. Little is known about the impacts of offshore wind farms on marine resource users in the United States. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…The positive sign for this variable is contrary to Ladenburg & Dubgaard's (2009) findings that frequent users of the coastal areas, specifically boaters and anglers, are generally more averse to wind farms. However, according to more recent research by Tenbrink & Dalton (2018) and Smythe et al (2018), the base of the turbines has served as an artificial reef for spearfishing, which can explain the positive WTP for fishing and boating in our specification. Additionally, frequent visitors may perceive the construction of the wind farm as a novel feature of their repeat recreational site.…”
Section: Regression Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…The positive sign for this variable is contrary to Ladenburg & Dubgaard's (2009) findings that frequent users of the coastal areas, specifically boaters and anglers, are generally more averse to wind farms. However, according to more recent research by Tenbrink & Dalton (2018) and Smythe et al (2018), the base of the turbines has served as an artificial reef for spearfishing, which can explain the positive WTP for fishing and boating in our specification. Additionally, frequent visitors may perceive the construction of the wind farm as a novel feature of their repeat recreational site.…”
Section: Regression Resultsmentioning
confidence: 70%
“…This finding conflicts with the stated preference studies that find wind farms to be a visual disamenity in other contexts (Bishop & Miller, 2007;Firestone, et al, 2018;Fooks et al, 2017;Krueger et al, 2011b;Ladenburg, 2009;Ladenburg & Dubgaard, 2007;Landry et al, 2012a;Lilley et al, 2010a), but is consistent with evidence from Block Island in particular. Since turbine construction, ferries and charter boats have added trip options to see the turbines up close and the wind farm is a popular option for recreational fishing (Smythe et al, 2018;Tenbrink & Dalton, 2018). The ferries and charter boats charge about $30 for a trip to the wind farm (Charters, n.d.; Ferry, n.d.).…”
Section: Regression Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that offshore wind farms can attract touristrelated activities, such as recreational fishing, because the wind farm acts as a novelty destination (Lilley et al, 2010;Smythe et al, 2018). For the Block Island Wind Farm, fishermen noticed an increase in recreational fishing in the area after the wind turbines were constructed with several fishermen explaining that the wind farm acted as destination for recreational fishermen in the area (ten Brink and Dalton, 2018).…”
Section: Perceived Benefits Of the Kitty Hawk Wind Leasementioning
confidence: 99%
“…This was a concern for commercial fishermen around the Block Island Wind Farm who thought that turbines could be a navigational hazard (ten Brink and Dalton, 2018).…”
Section: Perceived Impacts Of the Kitty Hawk Wind Leasementioning
confidence: 99%